AKTIVITAS CAR FREE DAY JALAN DIPONEGORO DAN GAJAH MADA KOTA PEKANBARU - Novita Cahyanti; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research have been at location of car free day on the Diponegoro and Gajah Mada street in the Pekanbaru city, the problems is (1) How to identifying activities at the car free day in the Diponegoro and Gajah Mada street in the city of Pekanbaru? (2) How to socialization and implementation control social at the car free day on the Diponegoro and Gajah Mada street in the Pekanbaru city? (3) How to compliance of trader on the comply of the rules by selling on the location of car free day on the Diponegoro and Gajah Mada in the Pekanbaru city?. This research is qualitative research. Population in this research is all people who were at the car free day on the Diponegoro and Gajah Mada street. Because of population in this research is much and then researcher using accidental sampling technique, that is 8 informans, they is 2 visitors, 2 trader, 2 parking officer, and 2 security. Method applied in doing this research is interview and observation. The result of show that the purpose of car free day in the Pekanbaru city almost achieve its goal, cause of people is very enthusiasm participate by doing varios of activities on car free day. people activities at the site of a car free day is light axercise as gymnastics, jogging, badminton, there is also the use of a car free day with a leisurely stroll or refreshing, there are also enjoying a wide variety of culinary on offer in the car free day. however to achieve that goal, government got some promblems like as emergence of street vendors which is could be obstructing of the purpose of car free day, as the location of the car free day becomes narrow and making these locations not condusive anymore because a lot of rubbish everywhere.The Keyword : The activity, car free day, and street vendors